2010
DOI: 10.1161/circinterventions.108.828335
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of Carotid Artery Stents to Manage Symptomatic Carotid Artery Stenosis and Factors That Affect Outcome

Abstract: Background-Limited data are available about the long-term outcomes of the use of carotid artery stents in symptomatic patients and the impact of patient variables on the durability of endovascular carotid procedures. Outcome data previously reported from registry series mix symptomatic and asymptomatic patients. We present analysis of long-term follow-up, with independent neurological assessment, for patients with symptomatic high-grade carotid lesions undergoing stenting to identify patients at risk of recurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…This is in line with previous studies and may be due to heavily calcified plaques, which made it difficult to establish an appropriate stent positioning without residual narrowing [13, 14]. Interestingly, in a study with 563 patients, Randall et al found that a residual stenosis of >50% after CAS is associated with an increased risk of ipsilateral stroke in the long run [15]. Therefore, pursuing an optimal stent deployment during CAS seems to be a worthwhile aim, although it is known that an aggressive postdilation bears the risk of distal embolization.…”
Section: Discussionsupporting
confidence: 83%
“…This is in line with previous studies and may be due to heavily calcified plaques, which made it difficult to establish an appropriate stent positioning without residual narrowing [13, 14]. Interestingly, in a study with 563 patients, Randall et al found that a residual stenosis of >50% after CAS is associated with an increased risk of ipsilateral stroke in the long run [15]. Therefore, pursuing an optimal stent deployment during CAS seems to be a worthwhile aim, although it is known that an aggressive postdilation bears the risk of distal embolization.…”
Section: Discussionsupporting
confidence: 83%
“…We selected subgroups based on factors shown to affect CAS performance in the literature or based on clinical knowledge. These factors included the following: sex (male or female), symptomatic status, [15][16][17][18][19][20] race (white or not white), type of CAS procedure (elective or nonelective), 14 age (66-69, 70-74, 75-79, or ≥80 years), 12,14,15,17,19,33 clinical trial enrollment status (enrolled or not enrolled), 16 and National Coverage Determination indication (high surgical risk with symptomatic carotid Median (IQR) 11 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) No. of past-year nursing home visits…”
Section: Subgroupsmentioning
confidence: 99%
“…To our knowledge, outcomes during and beyond the periprocedural period have not been described in real-world, contemporary Medicare populations. Also, little is known about the significance of patient characteristics, clinical indications, carotid stenosis characteristics, and center characteristics outside of the RCT setting 4,[7][8][9][10][11][12] or small prospective registry or single-center or dual-center studies [13][14][15][16] or how these characteristics affect CAS performance beyond the periprocedural period. 8, 10,[13][14][15][17][18][19][20] The objective of this study was to describe the incidence of outcomes overall and among subgroups of Medicare beneficiaries undergoing CAS.…”
mentioning
confidence: 99%
“…One of the major strengths of this study is that we were able to evaluate and adjust for important clinical and procedural factors, such as high surgical risk status 31 and symptomatic status, 32 which have been associated with poor outcomes after CAS. In using mortality as the outcome, we selected the hardest and most reliable end point.…”
Section: Strengths and Limitationsmentioning
confidence: 99%